IMPACTS OF CONCENTRATE FEEDING LEVEL WITH OR WITHOUT N-CARBAMYLGLUTAMATE ON PRODUCTIVE PERFORMANCE OF GOATS - Salam S. I,; J. A. Tawfeeq Al-Ani, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted to evaluate the effect of feeding three levels of concentrate 2%, 3%, and 4% with or without additives of N-carbamylglutamate (NCG) on the digestibility, feed efficiency, and daily gain of Shami goats. Twenty-four male goats were used aged 8-10 months with an initial weight 32.687 ± 1.52kg divided into six treatments in a 2×3 factorial experiment/ Completely Randomized Design. Individual feeding was used for 70 days preceded by 14 days as an adaptation period. The results of increasing concentrate showed a non-significant increase in nutrients intake with superiority of NCG treatments and a significant increase (P